1985
DOI: 10.2527/jas1985.6051110x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Double Decking and Space Allowance on the Performance and Behavior of Feeder Lambs1

Abstract: A 2 X 2 factorial experiment was conducted using growing lambs to compare single-level vs double-decked pens and high (.32 m2/lamb) vs low (.48 m2/lamb) densities. Three replicates of each treatment combination were involved using 30 lambs/pen. In the double-decked pens, an upper deck located over the rear section of the lower level provided one-third of the total floor area. Feed and water were provided on the lower level only and lambs could move freely between levels by means of a slatted ramp. All floors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Nevertheless, those studies used female adult sheep and the preferences of young lambs could be different, as reported by Teixeira et al (2013) in a multiple choice test that included several types of bedding. The EE lambs could have used FRA and PRA as activity areas because of their structural features and the natural inclination of lambs to climb on objects (Gonyou et al, 1985). The CO lambs used the FRA and PRA areas in the same way as the RM area, mainly to rest.…”
Section: Behavior and Use Of Spacementioning
confidence: 99%
“…Nevertheless, those studies used female adult sheep and the preferences of young lambs could be different, as reported by Teixeira et al (2013) in a multiple choice test that included several types of bedding. The EE lambs could have used FRA and PRA as activity areas because of their structural features and the natural inclination of lambs to climb on objects (Gonyou et al, 1985). The CO lambs used the FRA and PRA areas in the same way as the RM area, mainly to rest.…”
Section: Behavior and Use Of Spacementioning
confidence: 99%
“…Few studies relevant for Norwegian husbandry practices are conducted and most of the literature is old. Arehart et al (1969) found no effect of density in terms of differences in growth rate between two months old feedlot lambs in pens varying between 0.37 and 0.93 m 2 area per head, whereas Gonyou et al (1985) documented reduced growth of lambs in pens measuring 0.32 m 2 per lamb compared to 0.48 m 2 per lamb. Leme et al (2013) examined the effect of group size, and found that at the density of 2.4 m 2 per lamb, average weight gain tended to be higher for feedlot lambs in pens of two lambs compared to lambs housed in pens of ten.…”
Section: Space Allowance Indoorsmentioning
confidence: 90%
“…For an overview of behavioral data collection equipment see Martin and Bateson (1986) and Lehner (1979). Wood-Gush, 1954) Sequential contraints; rates; percent of time; durations; nearest neighbor relationships (e.g., Crowell-Davis et al, 1985) Synchrony; frequencies; rates; durations (e.g., Sweeting et al, 1985) Synchrony; percent of time; subgroup sampling (e.g., Gonyou et al, 1985).…”
Section: Data Collection Equipmentmentioning
confidence: 99%